Future Care Planning for patients approaching end-of-life with advanced heart disease: an interview study with patients, carers and healthcare professionals exploring the content, rationale and design of a randomised clinical trial. Issue 7 (14th July 2014) - Denvir, Martin A; Highet, Gill; Robertson, Shirley; Cudmore, Sarah; Reid, Janet; Ness, Andrea; Hogg, Karen; Weir, Christopher; Murray, Scott; Boyd, Kirsty
Abstract : Objective: To explore the optimal content and design of a clinical trial of an end-of-life intervention for advanced heart disease with patients, carers and healthcare professionals. Design: Qualitative interview and focus group study. Setting: Community and hospital-based focus groups and interviews. Participants: Stable community-dwelling patients, informal carers (PC, n=15) and primary and secondary care based healthcare professionals (HCP, n=11). Results: PC highlighted fragmentation of services and difficulty in accessing specialist care as key barriers to good care. They felt that time for discussion with HCP was inadequate within current National Health Service (NHS) healthcare systems. HCP highlighted uncertainty of prognosis, explaining mortality risk to patients and switching from curative to palliative approaches as key challenges. Patient selection, nature of the intervention and relevance of trial outcomes were identified by HCP as key challenges in the design of a clinical trial. Conclusions: PC and HCP expressed a number of concerns relevant to the nature and content of an end-of-life intervention for patients with advanced heart disease. The findings of this study are being used to support a phase II randomised clinical trial of Future Care Planning in advanced heart disease.